Field guide how to be a graphic designer - Labudovic, Ana (Rockport, 2009)
From the Publisher: This is the first and most complete handbook for the aspiring graphic designer. Fully illustrated with both contemporary and historical references, this book provides up and coming designers with all the practical insight they need to make it in the world of graphic design. From how to be more creative and how to stay on top creatively to the ins and outs of running a design business to the challenges of working in-house, this book will help anyone interested in graphic design decide on the right path for their career and give them the tools to make it into the career they want. The book provides inspiration from the top designers in the world on how they do what they do so well and also provides a complete reference of all the top design schools worldwide.